Processing and properties of Pb(Mg1/3Nb2/3)O3-PbTiO3-based ceramics - R. Wongmaneerung (2018)
Ceramic compositions of a combination between lead magnesium niobate, Pb(Mg1/3Nb2/3)O3, and lead titanate, PbTiO3, were fabricated using the Mg4Nb2O9 precursor technique. Their electrical properties with respect to temperature and frequency were examined and the effect of sintering conditions on phase formation, densification, microstructure and electrical properties of the ceramics were examined. It has been found that optimisation of sintering conditions can lead to a highly dense and pyrochlore-free PMN-PT ceramics. The gradual decrease of the physical properties of the sintered ceramics was related to the gradual decrease of density and inhomogeneous microstructure. The results also revealed that for the lower concentration of lead titanate, a relaxor behaviour is noticed with a high electrostrictive effect, which was almost hysteretic free. However, higher amount of lead titanate led to a normal ferroelectric behaviour. © 2008 Elsevier Ltd and Techna Group S.r.l.